Contribution of efflux pump hyperactivity to the resistance to new β-lactam-β-lactamase inhibitor combinations including ceftazidime-avibactam, aztreonam-avibactam, and imipenem-relebactam - Sung Pin Tseng; Tsung Ying Yang; Pu He; Yu Cin Deng; Po Liang Lu (Journal of Global Antimicrobial Resistance)
AIM: To investigate the resistance mechanisms of new β-lactam-β-lactamase inhibitor (β+βi) combinations in Enterobacterales isolates from Taiwan. BACKGROUND: New β+βi combinations, including ceftazidime-avibactam (CAZ-AVI), aztreonam-avibactam (AZT-AVI), and imipenem-relebactam (IMI-REL), are potential treatments for carbapenem-resistant Enterobacterales (CRE). METHODS: To explore their resistance mechanisms, 79 β+βi-resistant isolates (63 K. pneumoniae and 16 E. coli) from Taiwan (2012-2015) were analyzed. RESULTS: Resistance rates were 45.6% (36/79) for CAZ-AVI, 13.9% (11/79) for AZT-AVI, and 77.2% (61/79) for IMI-REL. Metallo-β-lactamase genes were the main resistance mechanism in 36 CAZ-AVI-resistant isolates, found in 50% of E. coli (8/16) and 19% of K. pneumoniae (12/63). AZT-AVI resistance (11 isolates) was primarily due to ESBL/AmpC combined with outer membrane protein (Omp) loss and pump hyperactivity, seen in 100% of E. coli (3/3) and 62.5% of K. pneumoniae (5/8). IMI-REL resistance (61 isolates) also involved ESBL/AmpC with Omp loss and pump hyperactivity in 58.3% of E. coli (7/12) and 59.2% of K. pneumoniae (29/49). Two isolates carried KPC-34 (271 ins KHSEAKDD, compared to KPC-2), possessing alteration near the 270-loop region, and KPC-17 accompanied by the OmpK35 loss was observed in the CAZ-AVI-resistant K. pneumoniae. Notably, two IMI-REL-resistant isolates were found with only pump hyperactivity, particularly the kpnF gene, indicating that efflux pumps without ESBL/AmpC may contribute to IMI-REL resistance. Overall, our study revealed a significant contribution of pump hyperactivity to the novel β+βi resistance (48/79, 60.8%). CONCLUSION: The current work provided new insights into novel β+βi-resistant mechanisms in Enterobacterales from Taiwan, highlighting the need for ongoing monitoring.